2003
DOI: 10.1179/016164103101201544
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal apolipoprotein E is not synthesized in neuron after focal ischemia in rat brain

Abstract: Apolipoprotein E (ApoE) is a major apolipoprotein in the central nervous system (CNS) that plays an important role in Alzheimer's disease. It may also be involved in other CNS disorders including ischemic injury. We investigated the changes of ApoE protein and mRNA expression in the brain with middle cerebral artery occlusion (MCAO) to clarify its origin after focal ischemia in rats. Increased ApoE immunoreactivity was recognized in astrocytes 3-14 days after MCAO in the affected side of cortex, and in neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
3
8
0
Order By: Relevance
“…Clusterin mRNA expression, in contrast to neuronal protein accumulation, appeared to be glial in origin with increases in mRNA in and around the hippocampus fissure and only a weak signal over the CA1 and CA2 pyramidal cell layer. These results support the theory that clusterin is synthesized in the astrocytes, secreted and then taken up by dying neurons [39]. Clusterin was accumulating in neurons destined to die by programmed cell death.…”
Section: P Pr Re Es Se En Ni Il LI In Ns Ssupporting
confidence: 87%
See 1 more Smart Citation
“…Clusterin mRNA expression, in contrast to neuronal protein accumulation, appeared to be glial in origin with increases in mRNA in and around the hippocampus fissure and only a weak signal over the CA1 and CA2 pyramidal cell layer. These results support the theory that clusterin is synthesized in the astrocytes, secreted and then taken up by dying neurons [39]. Clusterin was accumulating in neurons destined to die by programmed cell death.…”
Section: P Pr Re Es Se En Ni Il LI In Ns Ssupporting
confidence: 87%
“…In contrast, apolipoprotein E mRNA was expressed in astrocytes and macrophages but not in neurons. These results suggest that neuronal apolipoprotein E was not synthesized in neurons but derived from astrocytes [39]. Recent findings support this observation that astroglial cells regulate apolipoprotein E expression in neurons [16].…”
Section: P Pr Re Es Se En Ni Il LI In Ns Smentioning
confidence: 53%
“…Overexpression of apolipoprotein J mRNA in contrast to neuronal protein staining appeared to be glial in origin with increases in mRNA the hippocampus fissure and only a very weak signal over the CA1 and the CA2 pyramidal neuron layer. The above results support the idea that clusterin is synthesized in the astrocytes, secreted outside and next taken up by dying neurons (Nishio et al, 2003). Clusterin deposition was observed in neurons destined to die by apoptosis.…”
Section: Apolipoproteins After Ischemiasupporting
confidence: 78%
“…Some previous studies showed that at least some neurons express apoE (Diedrich et al, 1991;Poirier et al, 1991;Han et al, 1994;Bao et al, 1996;Metzger et al, 1996;Xu et al, 1996Xu et al, , 1999aDupont-Wallois et al, 1997;Boschert et al, 1999;Ferreira et al, 2000;Dekroon and Armati, 2001;Hartman et al, 2001;Aoki et al, 2003;Harris et al, 2003); others suggested that they do not (Page et al, 1998;Nishio et al, 2003). More recent studies suggest that neurons might not normally express apoE but do so in response to brain injuries, such as excitotoxic or ischemic injury (Boschert et al, 1999;Aoki et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although not all studies support the notion (Page et al, 1998;Nishio et al, 2003), increasing evidence suggests that under diverse pathophysiological conditions, CNS neurons also express apoE, albeit at lower levels than astrocytes (Diedrich et al, 1991;Han et al, 1994;Bao et al, 1996;Beffert and Poirier, 1996;Metzger et al, 1996;Xu et al, 1998Xu et al, , 1999a. The cellular origin of apoE appears to influence its effects on AD pathology Huang, 2006).…”
Section: Introductionmentioning
confidence: 99%